ANALISIS LAMA MENCARI KERJA BAGI TENAGA KERJA TERDIDIK DI KOTA BANDA ACEH - Fahira, Dhea (PENCERAHAN, 2023)
This research aims to analyze the factors that influence the length of time looking for work among educated workers in Banda Aceh City. This research is quantitative, using primary data with non-probability sampling obtained by distributing questionnaires to 108 respondents. The model used is the Multiple Linear Regression model. The research results show that education, age and work experience have a significant positive effect on the length of time workers look for work. The age variable is the most dominant variable influencing the length of time looking for work compared to education and work experience. It is hoped that the Government can develop apprenticeship programs that are relevant to higher education. This program can provide opportunities for new graduates to gain practical experience in the workplace and develop skills required by industry. The government can provide incentives for companies to participate in these programs, such as tax cuts or benefits.